Chapter Fly Ash as a Cementitious Material for Concrete - Li, Long-yuan (InTechOpen, 2020)
This paper presents a review on fly ash as prime materials used for geopolymer. Due to its advantages of abundant resources, less in cost, great workability and high physical properties, fly ash leads to achieving high mechanical properties. Fly ash is considered as one of the largest generated industrial solid wastes or so-called industrial by-products, around the world particularly in China, India, and USA. The characteristics of fly ash allow it to be a geotechnical material to produce geopolymer cement or concrete as an alternative of ordinary Portland cement. Many efforts are made in this direction to formulate a suitable mix design of fly ash-based geopolymer by focusing on fly ash as the main prime material. The physical properties, chemical compositions, and chemical activation of fly ash are analyzed and evaluated in this review paper. Reference has been made to different ASTM, ACI standards, and other researches work in geopolymer area.